ANALISIS LAYANAN DALAM MENINGKATKAN MINAT KONSUMEN (DI KANTIN PUTRA MA’HAD AL-MASHDUQIAH) - Devi Amaliya Putri (Lembaga Penerbitan, Penelitian, dan Pengabdian kepada Masyarakat (LP3M) of Institut Badri Mashduqi Probolinggo Jawa timur Indonesia, 2022)
At this time, the flow of information is growing rapidly. This also affects the development of the business world, where companies and business actors face increasingly greater challenges. And also business competition in the business world is getting tougher. A product that will be accepted and that will survive in the company's competition is a product that can provide maximum satisfaction to consumers. Humans are the main component in the formation of agencies or organizations, because in the implementation of services a business must be very responsible for providing good service to consumers. Customer satisfaction is an evaluation for the company, if customer satisfaction is achieved there will be loyalty from customers, therefore customer satisfaction is important for the company. Consumer satisfaction is dynamic, meaning that consumer expectations of a product or service will change over time. There are so many factors that can affect customer satisfaction. Companies today must be aware that consumers, especially customers today, are more concerned with service than the value of a product.